Immunotherapy for oncogenic-driven advanced non-small cell lung cancers: Is the time ripe for a change?. (December 2018) - Remon, J.; Hendriks, L.E.; Cabrera, C.; Reguart, N.; Besse, B.
Abstract: Immune checkpoint inhibitors (ICIs) have been incorporated in the treatment strategy of advanced non-small cell lung cancer (NSCLC) in first- and second-line setting improving the prognosis of these patients. However, the treatment landscape has been also drastically overturned with the advent of targeted therapies in oncogenic-addicted advanced NSCLC patients. Despite ICIs represent an active and new treatment option for a wide range of advanced NSCLC patients, the efficacy and the optimal place of ICI in the treatment strategy algorithm of oncogenic-addicted tumors remains still controversial, as only a minority of trials with ICI enrol oncogenic-addicted NSCLC patients previously treated with standard therapy. Therefore, there are still several open questions about ICI in oncogenic-driven NSCLC, such as the efficacy and toxicities, which need to be addressed before considering treatment with ICI as a standard approach in this population. It is in this framework, we provide a thorough overview on this currently controversial topic.